Membangun Pemahaman dan Empati: Peran Bimbingan Kelompok dalam Menyikapi Isu LGBT di Kalangan Remaja - Desvikayati, Ice; Nirwana, Herman; Hariko, Rezki; Fikri, Miftahul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The LGBT (Lesbian, Gay, Bisexual, and Transgender) phenomenon among adolescents is increasingly a concern in the educational environment. It emerges in adolescents’ social lives, both as part of self-identity and as an issue that raises pros and cons in school. The lack of understanding and empathy towards this issue often gives rise to discriminatory behaviors that negatively impact the psychosocial development of adolescents. This article lifts up the good practice of implementing group tutoring in schools as a strategic approach in building students’ understanding and empathy towards LGBT issues. Through descriptive qualitative methods and a participatory approach, this article highlights how group tutoring is a safe container for discussing, exploring values, as well as fostering inclusive attitudes among students. Results indicate that the implementation of structured and empathetic group tutoring is capable of reducing prejudice as well as forming tolerant attitudes toward diversity of sexual orientation and gender identity. The purpose of this article is to look at how group tutoring functions as an educational and preventive method in building students’ understanding and empathy towards LGBT issues. To achieve this goal, a literature study has been conducted that examines various methods of group tutoring, particularly those based on humanistic and social, in building inclusive attitudes among adolescents. Study results show that group tutoring helps teens understand diversity, become more empathetic, and makes schools safe and welcoming for all students, including LGBT students. This article emphasizes the role of kindergarten teachers in designing group tutoring programs that are sensitive to diversity issues to support adolescents’ social-emotional development.